Disruption of Trp53 in livers of mice induces formation of carcinomas with bilineal differentiation - Katz, Sarah-Fee; Schirmacher, Peter (Gastroenterology)
p53 limits the self-renewal of stem cells from various tissues. Loss of p53, in combination with other oncogenic events, results in aberrant self-rene…